Talking teenagers : information and inspiration for parents of teenagers with autism or Asperger's syndrome - Boushey, Ann, 1957- (Jessica Kingsley Publishers, 2007)
Ann Boushéy's teenage son Jon was diagnosed with high-functioning autism in kindergarten. Having mastered the day-to-day challenges that parenting a young child with autism or Asperger's Syndrome pose, Talking Teenagers considers questions surrounding parenting across the spectrum during the teenage years. Written out of her own experience, this inspirational book provides the information that will encourage other parents with teens on the autism spectrum. Covering everyday topics, from what to take on vacation and dealing with anger, to sex education and planning for the parents' own d.